Improving Students' Writing Skills in Procedure text through Teams Games Tournament (TGT) and Picture Series - Zakaria, Azman; Rosnija, Eni; Maryani, Maryani (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research aims to enhance students' skills in writing procedure texts using the Teams Games Tournament with Pictures Series. The subjects of this study were all 32 students in class IX D at SMPN 12 Pontianak. The writers employed Classroom Action Research conducted over two cycles, in which each cycle consisted of two meetings. The data were collected using observation checklists, field notes, and tests. Based on the findings of this study, it can be concluded that the use of Teams Games Tournament and Pictures Series were able to improve students' writing skills. This can be seen from the increasement of the students’ mean scores from 76.3 in Cycle 1 to 84.9 in Cycle 2. In addition to score improvement, student engagement and enthusiasm during the learning process also significantly increased. Therefore, the researcher recommends the teachers to utilize both of these strategies in order to enhance students' writing skills.